2015
DOI: 10.1073/pnas.1420536112
|View full text |Cite
|
Sign up to set email alerts
|

Improving recombinant Rubisco biogenesis, plant photosynthesis and growth by coexpressing its ancillary RAF1 chaperone

Abstract: Enabling improvements to crop yield and resource use by enhancing the catalysis of the photosynthetic CO 2 -fixing enzyme Rubisco has been a longstanding challenge. Efforts toward realization of this goal have been greatly assisted by advances in understanding the complexities of Rubisco's biogenesis in plastids and the development of tailored chloroplast transformation tools. Here we generate transplastomic tobacco genotypes expressing Arabidopsis Rubisco large subunits (AtL), both on their own (producing tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 34 publications
6
104
0
1
Order By: Relevance
“…For instance, there are only two common residues under positive selection out of 10 between this study and methodologically similar work with a different sampling design published earlier (Galmés et al, 2014c). This fact raises questions of epistatic interactions and residue coevolution within Rubisco (Wang et al, 2011) as well as residue coevolution and complementarity between Rubisco and its chaperones (Whitney et al, 2015), which both may prevent the evolution of identical amino acid replacements because of different genetic backgrounds.…”
Section: The Analysis Of Positive Selection In Branches Leading To Spmentioning
confidence: 56%
See 1 more Smart Citation
“…For instance, there are only two common residues under positive selection out of 10 between this study and methodologically similar work with a different sampling design published earlier (Galmés et al, 2014c). This fact raises questions of epistatic interactions and residue coevolution within Rubisco (Wang et al, 2011) as well as residue coevolution and complementarity between Rubisco and its chaperones (Whitney et al, 2015), which both may prevent the evolution of identical amino acid replacements because of different genetic backgrounds.…”
Section: The Analysis Of Positive Selection In Branches Leading To Spmentioning
confidence: 56%
“…The design of future attempts at Rubisco engineering in crops should be based on surveys of Rubisco catalytic and genetic diversity with a particular stress on relatives of the crops in question. Growing knowledge of the Rubisco catalytic spectrum combined with existing engineering toolkits for Rubisco (Whitney and Sharwood 2008) and its chaperones (Whitney et al, 2015) give us hope that the Rubisco efficiency, and hence the photosynthetic capacity, of crops could be improved in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…the conversion of C 3 crops to C 4 photosynthesis (Driever and Kromdijk, 2013). Direct replacement of Rubisco will also likely necessitate coengineering of ancillary proteins to achieve maximum results, as demonstrated recently through work with the cochaperone RAF1 (Whitney et al, 2015). The recent introduction of a faster cyanobacterial Rubisco that could sustain higher photosynthetic rates, albeit at high CO 2 concentrations (Lin et al, 2014b;Occhialini et al, 2016), confirms the feasibility and potential of interspecies Rubisco substitutions.…”
Section: Tailored Solutions Are Required For Optimizing Crop Carbon Amentioning
confidence: 90%
“…Potential unintended effects on assembly could be a factor when mutating residues known to be involved in interactions between the large and small subunits. Careful consideration must also be given to avoiding effects on holoenzyme assembly and compatibility with ancillary proteins or assembly chaperones (Carmo-Silva et al, 2015;Whitney et al, 2015). This presents a promising avenue for future work in model systems, testing these residues either singly or in combination, with previous studies having shown strong potential for modifying Rubisco catalysis with targeted amino acid substitutions (Whitney et al, 2011b).…”
Section: Targeting Improvements Through Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation